Becoming German : the 1709 Palatine migration to New York - Otterness, Philip (Cornell University Press, 2004)
"Becoming German tells the story of the largest and earliest mass movement of German-speaking immigrants to America. The so-called Palatine migration of 1709 began in the western part of the Holy Roman Empire, where perhaps as many as thirty thousand people left their homes, lured by rumors that Britain's Queen Anne would give them free passage overseas and land in America. They journeyed down the Rhine and eventually made their way to London, where they settled in refugee camps. The rumors of free passage and land proved false, but, in an attempt to clear the camps, the British government finally agreed to send about three thousand of the immigrants to New York in exchange for several years of labor